Dissolved organic carbon of rainfall in coastal urban hotspot area, southeast China: Variations, determinants, and sources - Qing Ma; Jie Zeng; Qixin Wu; Wanfa Wang; Shijun Mao; Zixuan Liu; Jingwen Chen; Zhiheng Ma; Zhong-Jun Wang; Xinyi He; Jie Zhang; Xin Ge (Journal of Hydrology: Regional Studies)
Study Region: This study is conducted in the southeastern coastal city of Fuzhou, China. Study Focus: Carbon emissions have significantly increased under the rapid urbanization. Wet deposition (rainwater) serves as a major sink for atmospheric organic carbon (OC) and acts as a potential source of dissolved organic carbon (DOC) in the Earth’surface. This study aims to clarify the status, variations, sources, and deposition flux in rainwater DOC in coastal urban hotspot area, in order to enhance the understanding of atmospheric OC in coastal area. New Hydrological Insights for the Region: The analysis revealed that the rainwater DOC volume-weighted mean (VWM) concentration during the study period was 1.77 mg C L-¹ , with an associated deposition flux of 2.02 g C m-² yr-¹ . The dilution effect of continuous precipitation affects the rainwater DOC concentrations. In addition, the concentration of rainwater DOC in Fuzhou was influenced by atmospheric OC from long-distance migration and local inputs. Characteristic ion ratios and positive matrix decomposition (PMF) model revealed that anthropogenic emissions driven by industrial activities, fossil fuel burning, and traffic contribute 93.7 % to rainwater DOC. The estimation of atmospheric wet deposition contributed 1.82 × 105 t yr−1 of OC to Taiwan Strait, dominating the external DOC input with a proportion of 67 %. This work gained insights into the wet deposition process of atmospheric OC in coastal cities and underscored the importance of this process in the global carbon cycle.